Pengaruh Pola Asuh Orang Tua terhadap Perkembangan Emosional Anak - Ghina Khoirun Nisa; Adejura Nurhalisa; Nafa Nafisah Ziaulhaq; Sri Mulyeni (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the influence of parenting styles on the emotional development of early childhood based on a literature review. Emotional development is a crucial aspect of character formation, emotional regulation, and children’s social skills in daily life. The research method employed is a literature review, which involves examining relevant sources such as academic journals, books, and research The methodology utilizes a synthesis of peer-reviewed journals and relevant publications concerning the impact of caregiving styles on early childhood emotional maturity The reviewed literature was analyzed descriptively to identify patterns and trends in previous research findings. The results of the literature review indicate that parenting styles have a significant influence on children’s emotional development. Democratic (authoritative) parenting is consistently found to have the most positive impact on children’s emotional development, including better emotional regulation, self-confidence, independence, empathy, and social competence. Children raised with democratic parenting tend to express their emotions in a healthy manner and adapt well to social environments. In contrast, authoritarian, permissive, and neglectful parenting styles are often associated with emotional difficulties, such as low social skills, poor self-control, and challenges in managing emotions. Based on these findings, it can be concluded that democratic parenting plays a vital role in supporting optimal emotional development in early childhood